Verdad: un debate tradicional revisado - Wright, Crispin (2007)
“Truth: A Traditional Debate Reviewed”. This paper proposes a critical review of the presuppositions at the background of the traditional discussion on truth. Despite acknowledging that the said discussion rationalizes many of the movements and tentatives of its main characters to clarify the facts, it isascertained that, since it is centered in a reductive analyses of truth, it is not apt to generate the most adequate interpretation of the same. The theories in dispute will be expounded and criticized: deflationism, intrinsicalism, and both forms of relationism –coherentism and correspondence. An alternative to theanalytical-theoretical approach to truth –which in its different guises has served as basis of the traditional debate– will be purported.